THE INFLUENCE OF FOMO AND BRAND IMAGE ON E-IMPULSE BUYING GOFOOD AT MIE GACOAN BANDUNG - Syifa Fauziah Hamidah; Roro Arinda Reswanti Julian Pratama; Lindi Utami Marquerette (UPT Publikasi Ilmiah UNISBA, 2025)
In the use of food delivery applications, FOMO (fear of missing out) often arises due to limited-time promotions and brand popularity. For example, Mie Gacoan, which has a strong brand image, is actually able to encourage consumers to make impulsive purchases. This study uses a quantitative approach with descriptive analysis. The data was processed using Microsoft Excel 2019 and SPSS 26 for Windows, while the survey was conducted by distributing questionnaires to GoFood users to determine how much influence FOMO and brand image have on online food purchases. The results show that both factors significantly influence the impulsive buying behavior of Mie Gacoan consumers in Bandung via GoFood. This finding confirms that a marketing strategy that emphasizes FOMO elements and strengthens brand image can be an effective way to increase impulsive sales on digital platforms.